1998
DOI: 10.1002/(sici)1097-0215(19980610)76:6<829::aid-ijc11>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase-type-plasminogen-activator(UPA) production by human breast (myo)fibroblastsin vitro: Influence of transforming growth factor-β1 (TGFβ1) compared with factor(s) released by human epithelial-carcinoma cells

Abstract: The urokinase‐type plasminogen activator (uPA) may be considered as a key enzyme in the processes of cancer cell invasion and metastasis. Evidence has been presented that, in breast stroma, uPA is expressed predominantly by myofibroblasts located at the invasive areas of the tumor. To examine whether transforming growth factor type‐1 (TGFβ1) produced by breast‐carcinoma cells is a candidate responsible for the induction of uPA‐producing myofibroblasts, we studied in vitro the capacity of normal and tumor‐deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 20 publications
1
28
1
Order By: Relevance
“…Interactions between epithelial cells and fibroblasts have a major role in many biological processes and it follows that the interactions between tumour cells and neighbouring myofibroblasts may be biologically significant, probably mediated by soluble factors such as growth factors and cytokines. This has been demonstrated previously in breast cancer where TGF-b1 produced by breast cancer cells activates normal breast stromal fibroblasts and promotes them to produce proteases (Ronnov-Jessen and Petersen, 1993;Sieuwerts et al, 1998). Similar interactions have been shown in prostatic carcinomas (Olumi et al, 1999;Webber et al, 1999), and in the fibrosis observed in organs such as the kidney (Lewis and Norman, 1998) and liver (Kinnman and Housset, 2002).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Interactions between epithelial cells and fibroblasts have a major role in many biological processes and it follows that the interactions between tumour cells and neighbouring myofibroblasts may be biologically significant, probably mediated by soluble factors such as growth factors and cytokines. This has been demonstrated previously in breast cancer where TGF-b1 produced by breast cancer cells activates normal breast stromal fibroblasts and promotes them to produce proteases (Ronnov-Jessen and Petersen, 1993;Sieuwerts et al, 1998). Similar interactions have been shown in prostatic carcinomas (Olumi et al, 1999;Webber et al, 1999), and in the fibrosis observed in organs such as the kidney (Lewis and Norman, 1998) and liver (Kinnman and Housset, 2002).…”
Section: Discussionsupporting
confidence: 70%
“…They upregulate the expression of serine and matrix metalloproteinases, which degrade and remodel extracellular matrix, possibly potentiating cell invasion and migration (Sieuwerts et al, 1998). In addition, Ramos et al (1997) showed that peritumour FCM upregulated the expression of the integrin avb6 in SCC cells, and we have previously demonstrated that de novo expression of this integrin promotes invasion of oral carcinoma (Thomas et al, 2001a, b).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The proinflammatory cytokines tumor necrosis factor-a (TNF-a) and transforming growth factor-b (TGF-b) play central roles in this process. Breast cancer cells induce uPA and MMP9 expression in stromal fibroblasts via secretion of TGF-b and/or TNF-a (Sieuwerts et al 1998;Stuelten et al 2005). Recent reports propose a shift from TGF-b signaling in primarily epithelial cells in normal and adenoma tissue to stromal cells (i.e., fibroblasts, T cells, macrophages, and endothelial cells), which promoted tumor invasion and metastasis (Calon et al 2012;Hawinkels et al 2014).…”
Section: Pericellular Proteolysis In the Tumor Microenvironmentmentioning
confidence: 99%
“…[25][26][27][28]30 Tumor cells can also regulate ECM degradation and tumor cell motility and invasion, either directly, by releasing proteolytic enzymes, or indirectly, by activating their expression in stromal cells. [31][32][33][34] The strong evidence that stromal cells can regulate breast carcinoma growth and invasion at the primary site prompted us to ask whether similar cell-cell interactions may also determine tumor take and progression within invaded regional lymph nodes. Studies based on leukemia and lymphoma models have demonstrated that lymph node stromal cells can provide growth-modulating and antiapoptotic signals to leukemic cells through cell-cell contact and the elaboration of soluble factors.…”
mentioning
confidence: 99%